2022
DOI: 10.6007/ijarbss/v12-i10/15386
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of Ergonomic Risk Factors and Occupational Safety and Health (OSH) Performance

Abstract: In Malaysia, studies have shown that low employee performance occurs due to accidents, health problems and stress at work. This situation affects the performance of the organization, reduces the quality of work, increases the cost of workers' compensation and ultimately interferes with the development of the organization and the growth of the national economy. This study aims to examine the level of employee awareness of ergonomic risk factors and occupational safety and health performance. A total of one hund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Conversely, implementing appropriate ergonomic measures can help mitigate these risks, promoting the employees' overall health and well-being. By reducing absenteeism, workflow disruptions are minimized, ensuring consistent job performance [52,53]. The long-term effects of working in an ergonomically optimized environment are particularly noteworthy [54].…”
Section: The Relationship Between Ergonomics and Job Performancementioning
confidence: 99%
“…Conversely, implementing appropriate ergonomic measures can help mitigate these risks, promoting the employees' overall health and well-being. By reducing absenteeism, workflow disruptions are minimized, ensuring consistent job performance [52,53]. The long-term effects of working in an ergonomically optimized environment are particularly noteworthy [54].…”
Section: The Relationship Between Ergonomics and Job Performancementioning
confidence: 99%
“…In Malaysia, studies have shown that low employee performance occurs due to accidents, health problems and stress at work. This situation affects the performance of the organization, reduces the quality of work, increases the cost of workers' compensation, and ultimately interferes with the development of the organization and the growth of the national economy (22).…”
Section: Introductionmentioning
confidence: 99%